2019
DOI: 10.1097/hcr.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Active Video Games as a Training Tool for Individuals With Chronic Respiratory Diseases

Abstract: Although the quality of evidence was low, in a small number of studies active video games induced peak heart rates and dyspnea levels comparable with traditional exercise training. Larger and longer-term randomized controlled trials are needed to establish the impact of video game training for individuals with chronic respiratory diseases.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Out of these studies, three were conducted in Australia [9,13,21], three were conducted in Brazil [7,24,26], two in Canada [6,22], one in Egypt [33], three in Italy [20,23,33], one in Ireland [25], one in the Netherlands [17], three in Spain [11,15,19], one in the UK [34], and four in the USA [35][36][37][38]. All eligible studies were published in English and were included in the quality analysis [27].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of these studies, three were conducted in Australia [9,13,21], three were conducted in Brazil [7,24,26], two in Canada [6,22], one in Egypt [33], three in Italy [20,23,33], one in Ireland [25], one in the Netherlands [17], three in Spain [11,15,19], one in the UK [34], and four in the USA [35][36][37][38]. All eligible studies were published in English and were included in the quality analysis [27].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The American College of Sports Medicine identified that modern technologies, including virtual reality, are the upcoming trend for rehabilitation and promoting an active lifestyle [5]. Based on their systematic review, Butler and colleagues conclude that active videogames induce similar physiological demands, such as maximal heart rate, dyspnea levels, and energy expenditure during training as traditional exercise modalities [6]. Obtaining clinical control, particularly in chronic respiratory conditions, can have systemic effects for the patient from length of hospital stay to quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os trabalhos apresentados a seguir discutem a eficácia da utilização destes jogos durante as sessões de terapia e a relevância de seu uso nos processos de telemedicina e reabilitação, lançando horizontes norteadores para este trabalho. O trabalho [Butler et al 2019] apresenta uma revisão sistemática que compara o treinamento ativo utilizando videogames (RV não imersiva) com o treinamento tradicional em pacientes com doenças respiratórias crônicas. Os resultados apontam que o uso de exergames podem trazer, no paciente, resultados fisiológicos semelhantes ao tratamento tradicional.…”
Section: Trabalhos Relacionadosunclassified